Tantangan dan Harapan Pembentukan Sistem Hukum Nasional - Rolib Sitorus (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
Community Service (PkM) activities as out-of-class learning in political life that is directly related to society. In Indonesia, the formation of national law is an integral part of the legal development process and Indonesia continues to strive to formulate a national legal system to replace the colonial legacy. The integration of various legal systems does not always run smoothly, in line with that the purpose of this writing is to find out the main challenges in the process of forming Indonesian national law, to find out the role of legislative institutions and public participation in forming responsive and just national law, as well as the hopes and strategies developed to realize the national legal system. The approach as a continuation of PkM activities is a normative legal review, namely a discussion that examines legal materials related to the formation of a national legal system. In efforts to form national law, challenges were found in harmonization, legal certainty, and legitimacy of the resulting legal products, weak legislative processes, overlapping regulations, and the influence of legal globalization. This is further exacerbated by the lack of public participation in the process of forming law, as well as limited human resources in law-making institutions. Great hopes for the renewal of national law towards a more democratic, responsive, and Pancasila-based direction. So it is necessary to codify the law, strengthen the legislative system, and national legal grand design.